GE_GERICHTE P/9775/2016 vom 18. Dezember 2018 - GE Cour de justice (2018)
LÉSION CORPORELLE PAR NÉGLIGENCE ; DISPOSITIONS PÉNALES DE LA LCR ; TORT MORAL | CP.125; CP.12.al3; LCR.31.al1; OCR.14; LCR.36.al1; CPP.429.al1